8(3n+5)=8(9n+9)+6

Simple and best practice solution for 8(3n+5)=8(9n+9)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(3n+5)=8(9n+9)+6 equation:


Simplifying
8(3n + 5) = 8(9n + 9) + 6

Reorder the terms:
8(5 + 3n) = 8(9n + 9) + 6
(5 * 8 + 3n * 8) = 8(9n + 9) + 6
(40 + 24n) = 8(9n + 9) + 6

Reorder the terms:
40 + 24n = 8(9 + 9n) + 6
40 + 24n = (9 * 8 + 9n * 8) + 6
40 + 24n = (72 + 72n) + 6

Reorder the terms:
40 + 24n = 72 + 6 + 72n

Combine like terms: 72 + 6 = 78
40 + 24n = 78 + 72n

Solving
40 + 24n = 78 + 72n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-72n' to each side of the equation.
40 + 24n + -72n = 78 + 72n + -72n

Combine like terms: 24n + -72n = -48n
40 + -48n = 78 + 72n + -72n

Combine like terms: 72n + -72n = 0
40 + -48n = 78 + 0
40 + -48n = 78

Add '-40' to each side of the equation.
40 + -40 + -48n = 78 + -40

Combine like terms: 40 + -40 = 0
0 + -48n = 78 + -40
-48n = 78 + -40

Combine like terms: 78 + -40 = 38
-48n = 38

Divide each side by '-48'.
n = -0.7916666667

Simplifying
n = -0.7916666667

See similar equations:

| In(x)=20 | | x+x*0.14=500 | | C=a+(n-8)dforn | | -6x-1=-6 | | 42/0.5= | | 2a+7=5a+9 | | 10r^2-2r=-4r+6 | | (x-6)*(x-6)=(x*x)-396 | | 45=2y | | 5x+43-2(x+7)=88-2x | | 0.16(y-2)+0.12y=0.20y-0.7 | | x^2-17X+3=0 | | 5x+43-2(x-7)=88-2x | | 8x^4+10x^3-14x^2-4x=0 | | 6x-3x=4x-1 | | y=4xn | | 2x^2-196-70x=0 | | 2y=.5x+6 | | x^3-klnx=0 | | x^3-klx=0 | | 2x-12=5x-43 | | 8x-5=2x-4.5 | | y=4x^2(5x-8) | | -8x^2+35x+-38=0 | | 1x+7=x+14 | | 22y=8y-98 | | 18x=150 | | 5y-9y=-14(-14) | | 8-x=4-.5x | | 12x+6=2x+26 | | 4x+50=13x-59 | | 0.50x+0.45(70)=34.5 |

Equations solver categories